Super‐Aligned Carbon Nanotube Films as Current Collectors for Lightweight and Flexible Lithium Ion Batteries. (19th October 2012) - Wang, Ke; Luo, Shu; Wu, Yang; He, Xingfeng; Zhao, Fei; Wang, Jiaping; Jiang, Kaili; Fan, Shoushan
Abstract Carbon nanotube (CNT) current collectors with excellent flexibility, extremely low density (0.04 mg cm−2), and tunable thickness are fabricated by cross‐stacking continuous CNT films drawn from super‐aligned CNT arrays. Compared with metal current collectors, better wetting, stronger adhesion, greater mechanical durability, and lower contact resistance are demonstrated at the electrode/CNT interface. Electrodes with CNT current collectors show improvements in cycling stability, rate capability, and gravimetric energy density over those with metal current collectors. These results suggest that CNT films can function as a promising type of current collector for lightweight and flexible lithium ion batteries with high energy density.